Sustainable strategy for corporate governance based on the sentiment analysis of financial reports with CSR - Yuan Song; Hongwei Wang; Maoran Zhu (Financial Innovation, 2018)
Focusing only on shareholders' financial return is not consistent with the concept of sustainable corporate governance. In contrast to financial performance, corporate social responsibility (CSR) is a non-financial performance index. Financial reports consist of both financial and non-financial disclosures. These disclosures help investors make decisions. This paper characterizes the interaction between the sentiment analysis of financial reports and CSR scores. The classification accuracy through SVM exceeds 86%. The empirical study shows that the financial report sentiment based on the PESTEL model, Porter's Five Forces model, and Value Chain (Primary and Support Activities) significantly correlates to the CSR score.
Keywords: 650; Financial report; CSR score; Sentiment analysis; Object library